2009
DOI: 10.1159/000203031
|View full text |Cite
|
Sign up to set email alerts
|

Figurunzufriedenheit von Frauen in Abhängigkeit vom Lebensalter: Normative Daten für den Fragebogen zum Figurbewusstsein

Abstract: Hintergrund: Der Fragebogen zum Figurbewusstsein (FFB) ist weit verbreitet für die Erfassung von Figurunzufriedenheit. Bisher liegen keine angemessenen Referenzwerte vor. Die vorliegende Untersuchung schlieβt diese Lücke und legt dabei ein besonderes Augenmerk auf den Zusammenhang zwischen Lebensalter und Figurunzufriedenheit. Material und Methoden: Der FFB wurde in einer repräsentativen Stichprobe von 1060 Frauen im Alter von 14–93 Jahren eingesetzt. Ergebnisse: Es zeigten sich nur kleine Unterschiede in der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…These studies have analyzed the impact of disease, chronic pain and disabilities on the development of body image (Barber et al, 2007;Browall et al, 2008;Ebbeskog & Ekman, 2001;Grimm, Novotny, Heberling, & Wirth, 2007;Haes, Curran, Aaronson, & Fentiman, 2003;Kornblith et al, 2007;Lieberman, Probart, & Schoenberg, 2003;Nordin et al, 2001;Tung & Targonski, 2005). The relationship and association between age and body dissatisfaction are also important topics in studies about body image of older adults (Barreto, Fernandes, & Guihard-Costa, 2011;Bedford & Johnson, 2006;Ferraro et al, 2008;Grippo & Hill, 2008;Halliwell & Dittmar, 2003;Pook, Braehler, & Tuschen-Caffier, 2009;Tiggemann, 2004;Ziebland, Robertson, Jay, & Neil, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have analyzed the impact of disease, chronic pain and disabilities on the development of body image (Barber et al, 2007;Browall et al, 2008;Ebbeskog & Ekman, 2001;Grimm, Novotny, Heberling, & Wirth, 2007;Haes, Curran, Aaronson, & Fentiman, 2003;Kornblith et al, 2007;Lieberman, Probart, & Schoenberg, 2003;Nordin et al, 2001;Tung & Targonski, 2005). The relationship and association between age and body dissatisfaction are also important topics in studies about body image of older adults (Barreto, Fernandes, & Guihard-Costa, 2011;Bedford & Johnson, 2006;Ferraro et al, 2008;Grippo & Hill, 2008;Halliwell & Dittmar, 2003;Pook, Braehler, & Tuschen-Caffier, 2009;Tiggemann, 2004;Ziebland, Robertson, Jay, & Neil, 2002).…”
Section: Introductionmentioning
confidence: 99%
“… Abbreviations: 95% CI, 95% confidence interval; AN, anorexia nervosa; BMI, body mass index; BSQ/FFB, Body Shape Questionnaire (Pook et al, 2009); CG, comparison group; d , Cohen's d ; EDE‐Q, Eating Disorder Examination Questionnaire (Fairburn & Beglin, 1994); M , mean value; SATAQ‐G, Sociocultural Attitudes Toward Appearance Questionnaires (Knauss et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…In addition to the demographic and clinical data, the German Version of the EDE‐Q, the German Version of the Body Shape Questionnaire (BSQ/FFB; Pook, Brähler, & Tuschen‐Caffier, 2009), and the German Version of the Sociocultural Attitudes Toward Appearance Questionnaires (SATAQ‐G; Knauss, Paxton, & Alsaker, 2007) were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, our findings are consistent with previous observations that the positive effects of pairing procedures on body dissatisfaction states are pronounced for individuals with pre-existing body image concern traits [ 20 ]. The moderated mediation patterns found here showed that only women with BSQ body image scores larger than 92, or EDE-Q8 scores larger 2.1, benefitted from successfully encoding the similar body → positive contingency (coincidentally, BSQ scores above 90 denote significant body image concerns according to normative data [ 47 ]. At the same time, many participants with low trait concerns (e.g., BSQ < 90) were still less than fully satisfied with their bodies prior to the intervention ( M = 1.4 out of − 4 to + 4 at BISS baseline), implying that the moderation is not merely an artefact of regression to the mean.…”
Section: Discussionmentioning
confidence: 99%